Improving dispersion and delamination of graphite in biodegradable starch materials via constructing cation-π interaction: Towards microwave shielding enhancement. (1st December 2022) - Yang, Yi; Tao, Jun-Ru; Yang, Dian; He, Qian-Ming; Chen, Xu-Dong; Wang, Ming
Highlights: Biodegradable graphite/starch materials with high EM shielding were prepared. Cation-π interaction improved delamination and dispersion of graphite in starch. Orientation of graphite was also very important to EM shielding performance. Cation-π interaction could enhance interfacial polarization of microwaves. Orientation of graphite endowed the Salisbury screen effect. Abstract: Herein, a low-cost, biodegradable, and high-performance microwave shielding graphite/starch material was fabricated via constructing a cation-π interaction between ammonium ions and graphite. The graphite flakes and starch were firstly mixed with distilled water containing ammonium hydroxide to form graphite/starch slurry under an ultrasonic assistant. The cation-π interaction could improve delamination degree and dispersion of graphite in starch matrix. The slurry was first used as a coating material on the surface of wood and paper to develop shielding packages. The effect of coating thickness and coating layers on EM shielding property of the materials was investigated. Second, the composites with a high orientation of graphite were fabricated by compression at high pressures. The electrical conductivity and EM shielding effectiveness (SET ) of the materials were greatly enhanced by construction of cation-π interaction and orientation of graphite. Specifically, the EM SET values increased from 56.9 to 66.8 dB for the composites with 50 wt.% graphite and 2.0 mm in thickness by constructing cation-π interaction. The EM SET values raised from 17.4 to 66.8 dB via the graphite orientation in the materials with the same components and thickness. The shielding mechanism of the compressed composites with orientation dispersion of graphite was also discussed in comparison to the coating layer with random dispersion of graphite. Graphical abstract: Image, graphical abstract